Optimization of Parameter for Submerged Lactic Acid Fermentation by Lactobacillus bulgaricus BS-18 - Singh, Birendra; Singh, S.P. (Asian Journal of Chemistry, 2010)
The optimization of parameters, viz., incubation period, temperature, pH and concentration of sucrose substrate have been studied for Lactoba-cillus bulgaricus BS-18. It has been found that submerged lactic acid fermentation attains its best activity when a 10.5% sucrose solution is allowed to ferment for 5 days at 48°C temperature by maintaining the pH value of the fermentation medium at 6.2.